Impacto do uso de realçador de sabor obtido de subproduto de cogumelo sobre a qualidade de hambúrguer bovino com redução de sódio - França, Fabiana (Universidade Federal de São Carlos, 2021)
Sodium has essential functions in the body, but its excessive ingestion can cause a series of chronic diseases, such as hypertension and cardiovascular problems. Due to this, the demand for low-salt meat products is increasing. One of the main alternatives to reduce sodium in these products is the use of flavor enhancers. Mushroom is known to be a natural flavor enhancer. During its harvest, part of the stipe is discarded, which could be used to obtain umami compounds. This study aimed to evaluate the impact of sodium reduction and the addition of natural flavor enhancer (RSN) obtained from mushroom stipe on the physicochemical and texture characteristics, as well as to evaluate the free amino acids content and the volatile compounds profile of beef burgers. After obtaining the RSN, it was applied in 2 concentrations in beef burgers with 3 levels of salt reduction, totaling 6 treatments, in addition to the control. The color of raw burgers was not affected by the formulations, whereas cooked burgers did not change their redness, but showed a slight increase in the L* and b* parameters. There was a slight increase in the pH of raw samples with the addition of the umami ingredient, but cooking minimized these differences. Water activity varied slightly between treatments, only for raw burgers. There was no effect of treatments on cooking loss and diameter reduction. The hardness and chewiness had their values reduced with the decrease of salt and increase of umami ingredient, resulting in softer burgers. The addition of RSN to beef burgers increased the content of the free amino acids proline and phenylalanine. The volatile profile of beef burgers showed a slight increase in compounds also found in the RSN, such as some aldehydes, alcohols and sulfur compounds. The results obtained show that the reduction of salt and the addition of a flavor enhancer obtained from shitake stipes is viable for application in beef burger, considering the physicochemical parameters, texture and the profile of free amino acids and volatile compounds, thus emphasizing the opportunity and the potential for the development of healthier burgers.
Impact of using a flavor enhancer obtained from mushroom by-product on the quality of sodium-reduced beef burger
Keywords: Lentinula edodes; Estipe de cogumelo; Realçador de sabor; Análise de Perfil de Textura; Aminoácidos livres; Compostos Voláteis; Mushroom stipe; Flavor enhancer; Texture Profile Analysis; Free amino acids; Volatile compounds; CIENCIAS AGRARIAS::CIENCIA E TECNOLOGIA DE ALIMENTOS::CIENCIA DE ALIMENTOS::AVALIACAO E CONTROLE DE QUALIDADE DE ALIMENTOS; CIENCIAS AGRARIAS::CIENCIA E TECNOLOGIA DE ALIMENTOS::CIENCIA DE ALIMENTOS::QUIMICA, FISICA, FISICO-QUIMICA E BIOQUIMICA DOS ALIM. E DAS MAT.-PRIMAS ALIMENTARES